Women's ways of making - Goggin, Maureen Daly; Rose, Shirley K. (Utah State University Press, 2021)
"Knowledge creation has been disparaged as inferior to other expressions. Favoring the hand over the eye (as this collection) problematizes the way the eye has been co-opted as mind's investigation tool. Other senses are keys to knowing one's materials. When these ways of knowing are engaged can make rhetorical practice understood"--